Physical Obstruction of Nasal Cavities With Subsequent Asphyxia, Causes Lethality of Rats in an Acute Inhalation Study With Hydrophobic HMDZ Surface-Treated Synthetic Amorphous Silica (SAS) - Krueger, Nils; Weber, Klaus; Warfving, Nils; Vitali, Alex; Nolde, Jürgen; Schuster, Tobias B.; Bruer, Gustav Gerd; Creutzenberg, Otto; Wessely, Benno; Stintz, Michael; Moise, Valerie; Kellert, Marco (Frontiers in Public Health, 2022)
The aim of the present study was to understand the mechanism of lethality associated with high dose inhalation of hydrophobic surface treated SAS observed in some acute inhalation studies. It could be demonstrated that physical obstruction of the upper respiratory tract (nasal cavities) caused effects observed. Hydrophobic surface-treated synthetic amorphous silica was inhaled (flow-past, nose-only) by six Wistar rats (three males and three females) in an acute toxicity study at a concentration of approximately 500 mg/m³ for four hours. Under the conditions of the test set-up, the concentration applied was found to be the highest that can be delivered to the test animal port without significant alteration of the aerosol size distribution over time. None of the test-material-exposed animals survived the observation time; three animals died between 2¾ hours after starting exposure and cessation of exposure at 3¼ hours, two died after transfer to their cages and the remaining animal was sacrificed due to its poor condition. Histology accomplished by energy dispersive X-ray (EDX) analysis demonstrated that test material particles agglomerated and formed a gel-like substrate that ultimately blocked the upper respiratory airways, which is fatal for the rat as an obligatory nose breather. This observation is in line with the findings reported by Hofmann et al. (2018) showing a correlation between lethality and hydrophobicity determined by contact angle measurement.